2006
DOI: 10.1088/0741-3335/48/5/008
|View full text |Cite
|
Sign up to set email alerts
|

A simple plasma diagnostic based on processing the electrical signals from coaxial discharges

Abstract: A technique for the determination of the inductance evolution in coaxial discharges based on measurements of the voltage between the electrodes and of the discharge current time derivative is presented and discussed. The technique is applied to measurements performed in a 5.7 kJ plasma focus device operating with deuterium filling in the 1-6 mbar range (which is the neutron yield range) and the obtained results are in good agreement with the expected evolution of a current sheet within the electrodes system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…Up to now there is no direct measurements of such resistance, the references found in the literature claiming its existence being based mainly on theoretical speculations and indirect experiments. In any case, as discussed in Bruzzone et al (2006), the values of ∆L p found in the present experiment are consistent with those expected for a typical pinch column, so that there is no reason to consider eventual anomalous resistivities.…”
Section: Direct Empirical Correlationssupporting
confidence: 90%
See 1 more Smart Citation
“…Up to now there is no direct measurements of such resistance, the references found in the literature claiming its existence being based mainly on theoretical speculations and indirect experiments. In any case, as discussed in Bruzzone et al (2006), the values of ∆L p found in the present experiment are consistent with those expected for a typical pinch column, so that there is no reason to consider eventual anomalous resistivities.…”
Section: Direct Empirical Correlationssupporting
confidence: 90%
“…Details of the experiment and L p (t) evaluation can be found in Bruzzone et al (2006). At each of the six initial filling pres- sure values mentioned above, ten consecutive shots were performed before evacuating the vacuum chamber.…”
Section: Direct Empirical Correlationsmentioning
confidence: 99%
“…3. Still, the gross features of the experimentally observed shape and position of the GV surface [18], of the current versus time profile [20] and inductance versus time profile [27] are reproduced.…”
Section: Overview Of the Gv Modelmentioning
confidence: 99%
“…In order to validate the model, the numerical results were compared with the experimental determination of the inductance evolution of the CS in discharges performed in a PF [10]. In that study, it was shown that the CS inductance L g can be calculated using the measurements of the voltage on the collector plates and the time derivative of the discharge current.…”
Section: Resultsmentioning
confidence: 99%